Multiband slot-loaded dipole antenna for wlan and lte-a applications - Al-Bawri, Samir Salem; Mohd Faizal, Jamlos; Soh, Ping Jack; Syed Alwee, Aljunid Syed Junid; Mohd Aminudin, Jamlos; Narbudowicz, Adam (Institution of Engineering and Technology, 2018)
A multiband printed dipole antenna for wireless local area network (WLAN) and long-term evolution-advanced (LTE-A) applications is investigated here. Its multiband characteristic is enabled by the Y-slot present in the upper arm of the dipole, while the antenna's dimensions are (0.08λo × 0.384λo) at the lowest operating frequency. It features bandwidth of 14.6% centred at 2.4 GHz, and ~30.5% centred at 5.5 GHz for WLAN operation. An additional bandwidth of 6.9% centred at 3.5 GHz supporting LTE-A applications is also featured. Besides being compact, the proposed antenna radiates omnidirectionally with a gain of up to 4.09 dBi. Simulations and measurements are in good agreement.